Galactomannan from flame tree (Delonix regia) seeds extraction, characterization and interaction with k-carrageenan - Potante, Jennifer P.
ABSTRACT A potential galactomannan was obtained from Delonix regia seeds using hot water extraction and alcohol precipitation. This method is simple, easy to perform and allowed in the food industry. The optimum extraction time at 80°C was determined to be 1 hour with a yield of 4.72 ± 0.65% and a viscosity of 57.33 ± 1.90 cps for a 1% solution. The extraction process was standardized using viscosity as parameter. The extracted galactomannan was characterized to have an average yield of 8.61% and viscosity of 44.67 ± 0.33 cps using the standardized extraction procedure. The chemical structure of the galactomannan was elucidated using Fourier Transform Infrared Spectroscopy (FTIR). Possible synergism of D. regia gum with κ-carrageenan was determined by mixing different ratios of κ-carrageenan and the extracted gum. It was found that synergism between the two hydrocolloids occur at a κ-carrageenana/galactomannan ratio of 3:1 with a total polymer concentration of 1.5%.